Cloud concepts for the public sector in Germany. Use cases. - (:unkn) unknown (My University, 2012)
This document provides a compendium of material. The intention is not to provide a comprehensive overview of current use case activities and their relation to on-going discussions in Germany on Cloud Computing for the public sector, but to offer a basis for publications dedicated to particular audiences and specific situations. Therefore, we tried to refrain from generic arguments but to give a variety of concrete examples which allow carrying the discussion of specific issues from a political and legal level down to their technical implementation. These usage scenarios provide also a context to understand and to classify the more atomic and technically oriented use cases taken from the National Institute of Standards and Technology NIST, the Distributed Management Task Force DMTF, the Cloud Computing Use Case Discussion Group CCUCDG, and Microsoft documents. They moreover identify requirements that are specific for a soft migration to Cloud Computing in thisapplication domain. Cloud Computing for the public administration is ambitious. Aspects such as legal frameworks, organizational structures, technological potential and constraints, security concerns, consolidation and data protection play a crucial role in the adoption of cloud computing in the public sector. Thus, the introduction of Cloud Computing depends on the solution of technical, organizational and legal issues. The example of the German public sector will serve as a basis for the evaluation of benefits and challenges of Cloud Computing by defining and analyzing a number of use case scenarios. Starting point is the analyses of Cloud Computing definitions and use cases, e.g. those provided by NIST, DMTF, CCUCDG, and Microsoft. In particular, a common actor model is synthesized and extended to meet the requirements of the German public sector. Moreover, a business model configuration will be introduced which outlines possible interactions between citizen, enterprises,and administrations. Furthermore, additional dimensions for the categorization of use cases are identified. Therefore, this work complements existing use case description by the above mentioned organizations towards an "eGovernment perspective" which necessarily has to go beyond business models and technical considerations. To evaluate this eGovernment perspective under consideration of the current state of applicability of Cloud Computing in the German public sector, a number of interviews with members of eGovernment service providers have been performed. The evaluation results are concluded in a set of theses. To give typical application examples of how Cloud Computing can be applied in the German public sector three usage scenarios have been described and analyzed. - Scenario 1 illustrates how data privacy issues can be resolved by separating between personal and nonpersonal (open) data. Governmental processes which do not rely on personal data can be hosted inpublic Cloud infrastructures. It provides the basis of a prototype implementation. - Scenario 2 shows how a Cloud service providing a secure document storage can provide seamless interaction between administrations, enterprises, and citizens, optimize governmental processes by delivering documents in a timely manner, and to enable inter-administration processes by the electronic exchange of documents. It is used as a basis for the definition of templates for the description of use cases and usage scenarios. - Scenario 3 outlines the idea of interweaving governmental processes and business processes of enterprises (e.g., SMEs) to provide a business incubator for those enterprises. The scenario imposes interesting questions on a collaborative lifecycle management between the several actors.
Keywords: Verwaltung; Informationstechnologie; Informationstechnologie; Kommunikationswissenschaft; Entwicklungstendenz; Cloud-Computing